The Discursive Construction of Cultural Differences - Mavropoulos, Sofia (Language at Work - Bridging Theory and Practice, 2008)
By understanding in depth the actual process of cultural difference creation, businessmen become equipped with a knowledgeable and erudite shield that helps them circumvent cultural misunderstandings that they might encounter in their everyday business transactions. Paying more attention to the actual wordings that the cultural actors use in these transactions could prove very advantageous for the outcome of any business interaction. Only by obtaining a deeper understanding of the origin and manifestation of the differences can the intercultural perplexities be transcended. Only through knowledge and appreciation of the differences, intercultural obstructions need not become a reality.